Polymerization under Hypersaline Conditions: A Robust Route to Phenolic Polymer‐Derived Carbon Aerogels. Issue 47 (8th September 2016) - Yu, Zhi‐Long; Li, Guan‐Cheng; Fechler, Nina; Yang, Ning; Ma, Zhi‐Yuan; Wang, Xin; Antonietti, Markus; Yu, Shu‐Hong
Abstract: Polymer‐derived carbon aerogels can be obtained by direct polymerization of monomers under hypersaline conditions using inorganic salts. This allows for significantly increased mechanical robustness and avoiding special drying processes. This concept was realized by conducting the polymerization of phenol–formaldehyde (PF) in the presence of ZnCl2 salt. Afterwards, the simultaneous carbonization and foaming process conveniently converts the PF monolith into a foam‐like carbon aerogel. ZnCl2 plays a key role, serving as dehydration agent, foaming agent, and porogen. The carbon aerogels thus obtained are of very low density (25 mg cm −3 ), high specific surface area (1340 m 2  g −1 ), and have a large micro‐ and mesopore volume (0.75 cm 3  g −1 ). The carbon aerogels show very promising potential in the separation/extraction of organic pollutants and for energy storage. Abstract : Rather salty : Carbon aerogels were obtained upon conducting the polymerization of phenol–formaldehyde (PF) resin under hypersaline conditions, for example, by using ZnCl2 . The simultaneous carbonization and foaming process conveniently converts the PF monoliths into foam‐like carbon aerogels.